Modified Playfair cryptosystem for improved data security - Esau Taiwo Oladipupo; Oluwakemi Christiana Abikoye (Institute of Advanced Engineering and Science, 2022)
Playfair is the earliest known classical block cipher which is capable of taking two characters as a unit in the process of encryption and decryption. However, the cipher is suffering from vulnerability to many cryptanalysis attacks due to a lack of confusion and diffusion properties, an inability to handle numbers and special characters in the process of encryption and decryption, and a host of other deficiencies. Although several modifications and improvements had been done by different researchers, the emphasis has been on the modification of the key matrix to accommodate more characters to increase the keyspace. No attention has been given to increment in the size of the block that the Playfair cipher can handle at a time. In this paper, a modified Playfair (MPF) cryptosystem that is capable of handling different block sizes with high diffusion and confusion properties is developed. cryptanalysis of the developed cryptosystem was carried out and the results show that the MPF cryptosystem is resistant to Known plaintext attack, chosen-plaintext attack, chosen ciphertext attack, frequency analysis attack, autocorrelation attack, differential cryptanalysis attacks, entropy attacks, brute force attack, and can handle variable block sizes.